Mean estimation in the simultaneous presence of measurement errors and non-response using optional RRT models under stratified sampling. Issue 17 (22nd November 2021) - Zhang, Qi; Khalil, Sadia; Gupta, Sat
Abstract : In this study, we discuss mean estimation of sensitive variables in the presence of measurement errors and non-response using Stratified Random Sampling, and present a comparison of the proposed estimator with some existing estimators.